1985
DOI: 10.1103/physrevlett.55.1369
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Gamow-Teller Transition Probabilities and (p, n) Cross Sections at Small Momentum Transfers

Abstract: Gamow-Teller transition probabilities are extracted for eight nuclei with masses between 3 = 13 and 39 from medium-energy (p, n) reactions via the distorted-wave impulse approximation, and compared with experimental P-decay and with free-nucleon transition probabilities. These comparisons indicate strongly that the renormalization of the Gamow-Teller operator needed for (p, n) reactions on finite nuclei is different from that needed for P decay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 18 publications
7
49
0
Order By: Relevance
“…It was possible to describe the difference by means of an empirical (p, n) operator. This operator was first introduced to explain cases where (p, n) GT strength was enhanced relative to beta decay [30].…”
Section: Discussionmentioning
confidence: 99%
“…It was possible to describe the difference by means of an empirical (p, n) operator. This operator was first introduced to explain cases where (p, n) GT strength was enhanced relative to beta decay [30].…”
Section: Discussionmentioning
confidence: 99%
“…Our calculations for at MeV agree well with the calculations of Watson et a/. (368) 18-7.20. These calculations were performed for a fixed electron energy of 500 MeV and the invariant mass of the recoil system was held constant, equivalent to a proton with kinetic energy MeV incident upon the ground state of Five sets of calculations are shown.…”
Section: Charge Exchange In Reactionssupporting
confidence: 90%
“…The bump was not seen at 25 MeV, but was prominent at 45 MeV. For 90 Zr the excitation energy of the centroid of the bump was close to that expected for a particle-hole state with configuration (πg 7/2 ) (vg 9/2 ) -1 , while the angular distribution of the cross section for the bump was similar to that for transitions to known 1 + states at lower excitation arising from the (πg 9/2 ) (vg 9/2 ) -1 configuration. Finally, the magnitude of the cross section was comparable to that predicted by DWIA calculations for a transition to the (πg 7/2 ) (πg 9/2 ) -1 configuration.…”
Section: Giant Resonances and Sum Rulesmentioning
confidence: 82%
“…However, in a study of the (p,n) reaction on targets of 48 Ca, 90 Zr, I20 Sn and 208 Pb at 25, 35 and 45 MeV at Michigan State University, Doering et al [28], observed a broad bump in the 0 o reaction cross section for excitation energies a few MeV above the known isobaric analogue resonance as shown in Fig. 2.2a.…”
Section: Giant Resonances and Sum Rulesmentioning
confidence: 92%
See 1 more Smart Citation